PENGARUH MODEL COOPERATIVE LEARNING TIPE TALKING STICK TERHADAP PENINGKATAN PENGETAHUAN BAHAYA MEROKOK PADA SISWA SMP - Masfufa, Erma Wahyu; Fathoni, Gusmery (Jurnal Kesehatan Mesencephalon, 2018)
Health education is an important role as preventive action, especially in adolescents about the dangers of smoking. Using the cooperative model type talking stick is expected to increase the knowledge of the dangers of smoking. Cooperative learning type talking stick model is a learning strategy with a number of students as a small group member, in the completion of group tasks each student group members should work together and help each other to understand the material. The purpose of this study is to determine the effect of cooperative learning type of talking stick to increase the knowledge of the danger of smoking on the students. The research design used was pre-experimental with one group pre-test and post-test design. The subjects of this study were grade VII students who smoked as many as 43 students were taken with total sampling method, and data analysis uses Wilcoxon Test. Wilcoxon test results with the SPSS program, obtained the value of knowledge variables, probability value = 0,000 and the value of Î± = 0.05 so that the value of p <Î± and sig value. (0.000) <0,05 can be deduced There is influence of cooperative learning type of talking stick model to increase knowledge of smoking hazard to Junior High School student.Â Keywords : Model of cooperative learning type talking stick, knowledge.